A review of demodulation techniques for amplitude-modulation atomic force microscopy - Ruppert, Michael G.; Harcombe, David M.; Ragazzon, Michael R. P.; Moheimani, S. O. Reza; Fleming, Andrew J. (Beilstein Journal of Nanotechnology, 2017)
In this review paper, traditional and novel demodulation methods applicable to amplitude-modulation atomic force microscopy are implemented on a widely used digital processing system. As a crucial bandwidth-limiting component in the z-axis feedback loop of an atomic force microscope, the purpose of the demodulator is to obtain estimates of amplitude and phase of the cantilever deflection signal in the presence of sensor noise or additional distinct frequency components. Specifically for modern multifrequency techniques, where higher harmonic and/or higher eigenmode contributions are present in the oscillation signal, the fidelity of the estimates obtained from some demodulation techniques is not guaranteed. To enable a rigorous comparison, the performance metrics tracking bandwidth, implementation complexity and sensitivity to other frequency components are experimentally evaluated for each method. Finally, the significance of an adequate demodulator bandwidth is highlighted during high-speed tapping-mode atomic force microscopy experiments in constant-height mode.
Keywords: amplitude estimation; atomic force microscopy; amplitude modulation; digital signal processing; field-programmable gate array

Communication systems - Haykin, S. (John Wiley & Sons, 2008)

Linear position sensors: theory and application - Nyce, D. S. (John Wiley & Sons, 2004)

Capacitive sensors: Design and Applications - Baxter, L. K. (Wiley-IEEE Press, 1996)

(untitled) - Fleming, A. J. (Sens. Actuators, A, 2013)

(untitled) - Tsui, D. C.; Stormer, H. L.; Gossard, A. C. (Phys. Rev. Lett., 1982)

(untitled) - Rugar, D.; Grütter, P. (Phys. Rev. Lett., 1991)

Detection, Estimation, and Modulation Theory, Part IV, Optimum Array Processing - van Trees, H. L. (John Wiley & Sons, 2004)

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - García, R.; Pérez, R. (Surf. Sci. Rep., 2002)

(untitled) - García, R.; Magerle, R.; Perez, R. (Nat. Mater., 2007)

(untitled) - Martin, Y.; Williams, C. C.; Wickramasinghe, H. K. (J. Appl. Phys., 1987)

(untitled) - Minne, S. C.; Soh, H. T.; Flueckiger, P.; Quate, C. F. (Appl. Phys. Lett., 1995)

(untitled) - Albrecht, T.; Grütter, P.; Horne, D.; Rugar, D. (J. Appl. Phys., 1991)

(untitled) - Fukuma, T.; Kilpatrick, J. I.; Jarvis, S. P. (Rev. Sci. Instrum., 2006)

(untitled) - Kodera, N.; Yamamoto, D.; Ishikawa, R.; Ando, T. (Nature, 2010)

(untitled) - Fantner, G. E.; Barbero, R. J.; Gray, D. S.; Belcher, A. M. (Nat. Nanotechnol., 2010)

(untitled) - Uchihashi, T.; Iino, R.; Ando, T.; Noji, H. (Science, 2011)

(untitled) - Casuso, I.; Khao, J.; Chami, M.; Paul-Gilloteaux, P.; Husain, M.; Duneau, J.-P.; Stahlberg, H.; Sturgis, J. N.; Scheuring, S. (Nat. Nanotechnol., 2012)

(untitled) - García, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Martínez, N. F.; Lozano, J. R.; Herruzo, E. T.; Garcia, F.; Richter, C.; Sulzbach, T.; Garcia, R. (Nanotechnology, 2008)

(untitled) - Herruzo, E. T.; Perrino, A. P.; Garcia, R. (Nat. Commun., 2014)

(untitled) - Solares, S. D.; An, S.; Long, C. J. (Beilstein J. Nanotechnol., 2014)

(untitled) - Stark, R. W.; Heckl, W. M. (Rev. Sci. Instrum., 2003)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

(untitled) - Raman, A.; Trigueros, S.; Cartagena, A.; Stevenson, A. P. Z.; Susilo, M.; Nauman, E.; Antoranz Contera, S. (Nat. Nanotechnol., 2011)

(untitled) - Platz, D.; Tholén, E. A.; Pesen, D.; Haviland, D. B. (Appl. Phys. Lett., 2008)

(untitled) - Dick, A. J.; Solares, S. D. (J. Comput. Nonlinear Dyn., 2010)

(untitled) - Forchheimer, D.; Forchheimer, R.; Haviland, D. B. (Nat. Commun., 2015)

RMS to DC Conversion Application Guide - Kitchin, C.; Counts, L. (Analog Devices, Inc., 1986)

(untitled) - Cosens, C. R. (Proc. Phys. Soc., London, 1934)

(untitled) - Michels, W. C.; Curtis, N. L. (Rev. Sci. Instrum., 1941)

(untitled) - Morris, E. D.; Johnston, H. S. (Rev. Sci. Instrum., 1968)

Proceedings of the IEEE - Razavi, B. (Architectures and circuits for RF CMOS receivers, Custom Integrated Circuits Conference, 1998, 14.5.1998, 1998)

(untitled) - Karvinen, K. S.; Moheimani, S. O. R. (Mechatronics, 2014)

(untitled) - Karvinen, K. S.; Moheimani, S. O. R. (Rev. Sci. Instrum., 2014)

(untitled) - Ando, T.; Uchihashi, T.; Fukuma, T. (Prog. Surf. Sci., 2008)

(untitled) - Ando, T. (Nanotechnology, 2012)

(untitled) - Ando, T.; Kodera, N.; Takai, E.; Maruyama, D.; Saito, K.; Toda, A. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Uchihashi, T.; Ando, T.; Yamashita, H. (Appl. Phys. Lett., 2006)

(untitled) - Kokavecz, J.; Tóth, Z.; Horváth, Z.; Heszler, P.; Mechler, Á. (Nanotechnology, 2006)

(untitled) - Abramovitch, D. Y. (Coherent Demodulation with Reduced Latency Adapted for use in Scanning Probe Microscopes, 2010)

American Control Conference (ACC) - Abramovitch, D. Y. (Low latency demodulation for Atomic Force Microscopes, Part I efficient real-time integration, 29.6.2011-1.7.2011, 2011)

Proceedings of the 18th IFAC World Congress - Abramovitch, D. Y. (Low latency demodulation for atomic force microscopes, Part II: Efficient calculation of magnitude and phase, 2011)

(untitled) - Ruppert, M. G.; Karvinen, K. S.; Wiggins, S. L.; Reza Moheimani, S. O. (IEEE Trans. Control Syst. Technol., 2016)

American Control Conference (ACC) - Ragazzon, M. R. P.; Gravdahl, J. T.; Fleming, A. J. (On Amplitude Estimation for High-Speed Atomic Force Microscopy, 6.7.2016-8.7.2016, 2016)

(untitled) - Ragazzon, M. R. P.; Ruppert, M. G.; Harcombe, D. M.; Fleming, A. J.; Gravdahl, J. T. (IEEE Trans. Control Syst. Technol., 2017)

American Control Conference (ACC) - Ruppert, M. G.; Harcombe, D. M.; Moheimani, S. O. R. (State estimation for high-speed multifrequency atomic force microscopy, 6.7.2016-8.7.2016, 2016)

(untitled) - Ruppert, M. G.; Harcombe, D. M.; Moheimani, S. O. R. (IEEE/ASME Trans. Mechatronics, 2016)

Advanced Intelligent Mechatronics - Harcombe, D. M.; Ruppert, M. G.; Fleming, A. J. (Higher-harmonic AFM Imaging with a High-Bandwidth Multifrequency Lyapunov Filter, IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2017)

(untitled) - Sahoo, D. R.; Sebastian, A.; Salapaka, M. V. (Appl. Phys. Lett., 2003)

Proceedings of the IEEE Conference on Decision and Control - Sebastian, A.; Sahoo, D. R.; Salapaka, M. V. (An observer based sample detection scheme for atomic force microscopy, 2003)

(untitled) - Sahoo, D. R.; Sebastian, A.; Salapaka, M. V. (Int. J. Robust Nonlinear Control, 2005)

American Control Conference (ACC), 2007 - Sahoo, D. R.; Agarwal, P.; Salapaka, M. V. (Transient Force Atomic Force Microscopy: A New Nano-Interrogation Method, 2007)

(untitled) - Karvinen, K. S.; Ruppert, M. G.; Mahata, K.; Moheimani, S. O. R. (IEEE Trans. Nanotechnol., 2014)

(untitled) - Volder, J. E. (IRE Trans. Electron. Comput., 1959)

(untitled) - Lau, K.; Quevedo, D.; Vautier, B.; Goodwin, G.; Moheimani, S. (Control Eng. Practice, 2007)

Discrete-time signal processing - Oppenheim, A. V.; Schafer, R. W. (Prentice-Hall, 1989)

(untitled) - Kalman, R. E. (Trans. ASME, 1960)

Optimal filtering - Anderson, B. D. O.; Moore, J. B. (Dover Publications, 1979)

Fundamentals of Kalman Filtering: A Practical Approach - Zarchan, P.; Musoff, H. (American Institute of Aeronautics and Astronautics, Inc., 2000)

(untitled) - Girgis, A. A.; Hwang, T. L. (IEEE Trans. Power Appar. Syst., 1984)

Introduction to Random Signals and Applied Kalman Filterings - Brown, R. G.; Hwang, P. Y. C. (John Wiley & Sons, 1997)

Optimal State Estimation: Kalman, H-Infinity, And Nonlinear Approaches - Simon, D. (John Wiley & Sons, 2006)

Robust adaptive control - Ioannou, P. A.; Sun, J. (Dover Publications, Inc., 2012)

(untitled) - Pawłowski, S.; Dobiński, G.; Szmaja, W.; Majcher, A.; Smolny, M. (Sens. Actuators, A, 2015)

(untitled) - Monmasson, E.; Cirstea, M. N. (IEEE Trans. Ind. Electron., 2007)

Design, Modeling and Control of Nanopositioning Systems - Fleming, A. J.; Leang, K. K. (Springer, 2014)

(untitled) - Ruppert, M. G.; Moheimani, S. O. R. (IEEE Trans. Control Syst. Technol., 2016)